Non-immunogenic Induced Pluripotent Stem Cells, a Promising Way Forward for Allogenic Transplantations for Neurological Disorders - Frederiksen, Henriette Reventlow; Doehn, Ulrik; Tveden-Nyborg, Pernille; Freude, Kristine K. (Frontiers in Genome Editing, 2021)
Neurological disorder is a general term used for diseases affecting the function of the brain and nervous system. Those include a broad range of diseases from developmental disorders (e.g. Autism) over injury related disorders (e.g. stroke and brain tumors) to age related neurodegeneration (e.g. Alzheimer’s disease), affecting up to 1 billion people worldwide. For most of those disorders, no curative treatment exists leaving symptomatic treatment as the primary mean of alleviation. Human induced pluripotent stem cells (hiPSC) in combination with animal models have been instrumental to foster our understanding of underlying disease mechanisms in the brain. Of specific interest are patient derived hiPSC which allow for targeted gene editing in the cases of known mutations. Such personalized treatment would include 1) acquisition of primary cells from the patient, 2) reprogramming of those into hiPSC via non-integrative methods, 3) corrective intervention via CRISPR-Cas9 gene editing of mutations, 4) quality control to ensure successful correction and absence of off target effects and 5) subsequent transplantation of hiPSC or pre-differentiated precursor cells for cell replacement therapies. This would be the ideal scenario but it is time consuming and expensive. Therefore, it would be of great benefit if transplanted hiPSC could be modulated to become invisible to the recipient’s immune system, avoiding graft rejection and allowing for allogenic transplantations. This review will focus on the current status of gene editing to generate non-immunogenic hiPSC and how these cells can be used to treat neurological disorders by using cell replacement therapy. By providing an overview of current limitations and challenges in stem cell replacement therapies and the treatment of neurological disorders, this review outlines how gene editing and non-immunogenic hiPSC can contribute and pave the road for new therapeutic advances. Finally, the combination of using non-immunogenic hiPSC and in vivo animal modelling will highlight the importance of models with translational value for safety efficacy testing; before embarking on human trials.